Determinants of financial performance on tax avoidance moderated by transfer pricing (empirical study on energy companies listed on IDX 2018 - 2022) - Indupurnahayu; Renea Shinta Aminda; Immas Nurhayati; Widyatmanto Setyawan (Technium Business and Management, 2023)
The problem in the object of this study is about Company Size, receivables, debt, costs, and profits against tax avoidance and how the results when moderated transfer pricing. The study aims to analyze company size, receivables, debt, costs, profits against tax avoidance through transfer pricing. The research method used is quantitative method with secondary data. Data collection through interview techniques and documentation data collection by recording or collecting data on energy companies listed on the IDX for 2018-2022. From a population of 82 companies, a sample of 52 companies was obtained using purposive sampling according to criteria. Testing panel data regression model data with Chow Test and Hausman Test techniques using E-views application. The results prove that the performance of energy companies: Company Size, receivables, debts, costs, and profits have a significant positive effect on tax avoidance, and transfer pricing moderation positively affects the financial performance of energy companies on tax avoidance.